Trends in the psychosocial and mental health of HIV‐positive women in China from 2015 to 2020: Results from two cross‐sectional surveys - Qian Wang; Vivian W. I. Fong; Qinghua Qin; Hui Yao; Jiarui Zheng; Xiaoyan Wang; Ailing Wang; Qun Gao; Phoenix K. H. Mo (Wiley, 2022)
Abstract Background The human immunodeficiency virus (HIV) continues to be one of the major public health challenges in the world. Despite the advancement in medication and changes in views towards HIV in Chinese society, little is known about the changes in the psychosocial and mental health of HIV‐positive women in recent years. Objectives The present study examined the change in depression, anxiety, stigma, relationship with the child, intimacy with a partner, and social support from family, friends, and health professionals, for HIV‐positive women in China from 2015 to 2020. Methods Two cross‐sectional surveys were conducted in 2015 and 2020, and 429 and 382 HIV‐positive women were recruited from the Women's Health Department in Yunnan and Guangxi, China between November 2015 to May 2016, and November 2019 to January 2020, respectively. Results After controlling for significant sociodemographic variables, participants recruited in 2019-2020 had significantly lower levels of depression and anxiety and higher scores on emotional and tangible support from friends. On the other hand, they had lower scores in intimacy with partners and emotional and tangible support from family. No significant changes were found in stigma, relationship with the child, and support from health professionals. Conclusion Results provide important information on the changes in psychosocial and mental health, which offer insights into the design of interventions to promote psychosocial and mental health among HIV‐positive women in China. Patient or Public Contribution HIV‐positive women contributed to the data of this study. Health care professionals were involved in the discussion of the methods and results.